Flood Tolerance of Seeds and Seedlings of Three Native Forest Species of South America - Kubota, Victoria R. (2020)
[Introduction]: In the last decades, several countries of South America registered intense rainfalls and floods affecting riparian and gallery forests. Yet knowledge of the flooding tolerance of forest species is very limited. [Objective]: This study aimed to evaluate seeds and seedlings behavior of Luehea divaricata Mart., Parapiptadenia rigida (Benth.) Brenan, and Guibourtia hymenaeifolia (Moric.) J. Léonard exposed to ex-situ flooding regimes. [Methods]: Seeds of the selected species were immersed in water over seven different periods. After immersion seeds were sown, and their germination percentage and seedlings survival were evaluated for 30 days. [Results]: L. divaricata reduced its germination rate during the experiment from 45.9 % to 23.1 %. One fifth of the seeds of this species kept the germination capability even after 30 days of the immersion treatment. A visible loss of the germination capability and seedling survival was observed in P. rigida and G. hymenaeifolia when the immersion period exceeded five days. [Conclusions]: The response of seeds to immersions varied between species, being L. divaricata the species with better tolerance to flooding conditions.